Philanthropic hospitals and the operation of provider-owned health plans in Brazil - Lima, Sheyla Maria Lemos; Portela, Margareth C; Ugá, Maria Alicia Dominguez; Barbosa, Pedro Ribeiro; Gerschman, Silvia; Vasconcellos, Miguel Murat (Revista de Saúde Pública, 2007)
OBJECTIVE: To describe the management performance of philanthropic hospitals that operate their own health plans, in comparison with philanthropic hospitals as a whole in Brazil. METHODS: The managerial structures of philanthropic hospitals that operated their own health plans were compared with those seen in a representative group from the philanthropic hospital sector, in six dimensions: management and planning, economics and finance, human resources, technical services, logistics services and information technology. Data from a random sample of 69 hospitals within the philanthropic hospital sector and 94 philanthropic hospitals that operate their own health plans were evaluated. In both cases, only the hospitals with less than 599 beds were included. RESULTS: The results identified for the hospitals that operate their own health plans were more positive in all the managerial dimensions compared. In particular, the economics and finance and information technology dimensions were highlighted, for which more than 50% of the hospitals that operated their own health plans presented almost all the conditions considered. CONCLUSIONS: The philanthropic hospital sector is important in providing services to the Brazilian Health System (SUS). The challenges in maintaining and developing these hospitals impose the need to find alternatives. Stimulation of a public-private partnership in this segment, by means of operating provider-owned health plans or providing services to other health plans that work together with SUS, is a field that deserves more in-depth analysis.